Análise de fadiga e corrosão em dutos submarinos - Gomes Filho, Flávio Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Oil industry moves billions of dollars every year and is responsible for a big portion of power generation around the world. It's extraction and transport are very sensitive processes, cause any problems may cause big environmental catastrophes. This paper takes base on that to evaluate the resistance of steel tubes used for oil prospection to fatigues stresses caused by vortex-induced vibrations (VIV's) associated to superficial wear caused by corrosion. The study was elaborated by comparing the curve stress versus number of cicles of specimens with and without corrosion, obtained from an API 5CT T95 (1% Cr) pipe. The tests were hold in laboratory and the forced corrosion in salt spray chamber. To complement the results of the fatigue assay, microhardness and surface roughness tests were performed and microestructural analysis made using optical and electron microscopy. As expected, the corroded specimens had an increase on roughness levels and a reduction on fatigue life if compared to the ones without corrosion, mainly in higher tensions. Microroughness and optical microscopy analysis showed that the microstructure of the pipe is anisotropic in longitudinal and transversal ways

A indústria do petróleo movimenta bilhões de dólares todo ano e é responsável por grande parte da geração de energia no mundo. Sua extração e transporte são processos bastante sensíveis, pois quaisquer problemas podem causar grandes catástrofes ambientais. Este trabalho parte dessa motivação para avaliar a resistência de tubos de prospecção de petróleo aos esforços de fadiga, gerados por vibrações induzidas por vórtices (VIV's) em alto mar, associada ao desgaste superficial causado pela corrosão, fenômeno agravado neste meio. O estudo se baseou na comparação da curva Tensão x Números de Ciclos de corpos de prova com e sem corrosão, retirados de um tubo API 5CT T95 (1% Cr). Os ensaios de fadiga foram realizados em laboratório e a corrosão forçada ocorreu em câmara salina de salt-spray. Para complementar os resultados obtidos no ensaio de fadiga, foram ainda feitos ensaio de microdureza, rugosidade superficial, avaliação de perda de massa, microscopia eletrônica de varredura e microscopia óptica. Como esperado, os corpos de prova corroídos apresentaram um aumento de rugosidade e uma redução na vida em fadiga se comparados com os corpos de prova sem corrosão, principalmente para tensões mais altas. Os ensaios de microdureza e microscopia óptica demonstraram anisotropia entre os sentidos transversal e longitudinal do tubo
Keywords: Fadiga; Corrosão; Petróleo; Tubos; Fatigue